Drama and the transfer of power in Renaissance England - Wiggins, Martin (Oxford : Oxford University Press, 2012)
The state is at its most volatile when supreme power changes hands. This book studies five such moments of transfer in the sixteenth and early seventeenth centuries, from Henry VIII to the English Revolution, paying particular attention to the political function and agency of drama in smoothing the transition.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; English drama -- 17th century -- History and criticism; Politics and literature -- England -- History -- 16th century; Politics and literature -- England -- History -- 17th century; Theater -- Political aspects -- England -- History -- 16th century; Theater -- Political aspects -- England -- History -- 17th century; Great Britain -- Politics and government -- 1485-1603.; Great Britain -- Politics and government -- 1603-1649.